Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1532-5415.2005.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Cardiorespiratory Fitness in Well‐Functioning Older Adults: Treadmill Validation of the Long Distance Corridor Walk

Abstract: A 400-m walk performed as part of the LDCW provides a valid estimate of peak VO2 in older adults. Incorporating low-cost, safe assessments of fitness in clinical and research settings can identify early evidence of physical decline and individuals who may benefit from therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
164
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 26 publications
9
164
1
4
Order By: Relevance
“…The LDCW and cardiorespiratory testing was performed in 102 healthy adults aged 60 to 91 years and showed a strong correlation between 400-meter time and VO2peak (-0.79) [24]. In a final model that also included stride length, ending systolic blood pressure, and a nonlinear correction factor, the 400-meter time explained 62.5% of the variance in VO2peak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The LDCW and cardiorespiratory testing was performed in 102 healthy adults aged 60 to 91 years and showed a strong correlation between 400-meter time and VO2peak (-0.79) [24]. In a final model that also included stride length, ending systolic blood pressure, and a nonlinear correction factor, the 400-meter time explained 62.5% of the variance in VO2peak.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small and homogeneous study population, the findings have several important Six-minute walk (6-MW); long distance corridor walk (LDCW) * Student's t-test Aging the mean time in the 400-meter walk is 4.07 minutes [24]. In community dwelling elderly adults each increased minute to perform the 400-meter walk is associated with a 29% increased mortality risk and 52% increased risk of mobility limitations [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 This test for older adults has been shown to be a strong predictor of mortality, cardiovascular disease and mobility limitations in older adults. [59][60][61] Further, a recent study using an animal model has found that aerobic exercise has the potential to provide a protective effect against cardiac dysfunction during ADT. 62 Thus, aerobic and resistance exercise may be an effective method to minimize or overcome ADT cardiovascular-related toxicities.…”
Section: Physical Exercise As Potential Countermeasurementioning
confidence: 99%
“…Koster and colleagues 12 evaluated the ability of physical fitness to predict subsequent changes in body composition and muscle strength. The observation that physical fitness (as measured according to ability and time needed to complete a 400-m walk) 13,14 is related to differences in body composition and muscle strength is interesting but not particularly surprising. The major novel contribution of this study lies in the investigators' capacity to provide longitudinal data that, when stratified according to physical fitness, provides a dramatic illustration of the tremendous physiological variability and plasticity that different subsets of older adults experience as they age.…”
mentioning
confidence: 99%